Acetylcholinesterase Inhibition of Diversely Functionalized Quinolinones for Alzheimer's Disease Therapy - Bautista-Aguilera, Óscar M; Ismaili, Lhassane; Chioua, Mourad; Andrys, Rudolf; Schmidt, Monika; Bzonek, Petr; Martínez-Grau, María Ángeles; Beadle, Christopher D; Vetman, Tatiana; López-Muñoz, Francisco; Iriepa, Isabel; Refouvelet, Bernard; et al. (International journal of molecular sciences, 2020)
In this communication, we report the synthesis and cholinesterase (ChE)/monoamine oxidase (MAO) inhibition of 19 quinolinones (QN1-19) and 13 dihydroquinolinones (DQN1-13) designed as potential multitarget small molecules (MSM) for Alzheimer's disease therapy. Contrary to our expectations, none of them showed significant human recombinant MAO inhibition, but compounds QN8, QN9, and DQN7 displayed promising human recombinant acetylcholinesterase (hrAChE) and butyrylcholinesterase (hrBuChE) inhibition. In particular, molecule QN8 was found to be a potent and quite selective non-competitive inhibitor of hrAChE (IC50 = 0.29 μM), with Ki value in nanomolar range (79 nM). Pertinent docking analysis confirmed this result, suggesting that this ligand is an interesting hit for further investigation.
Keywords: Monoamine Oxidase; chinolony; Acetylcholinesterase; Quinolones; Kinetics; Monoamine Oxidase Inhibitors; Inhibitory Concentration 50; simulace molekulového dockingu; Structure-Activity Relationship; lidé; rekombinantní proteiny; Recombinant Proteins; inhibiční koncentrace 50; Drug Evaluation, Preclinical; monoaminoxidasa; Ligands; magnetická rezonanční spektroskopie; preklinické hodnocení léčiv; racionální návrh léčiv; acetylcholinesterasa; inhibitory MAO; Alzheimer Disease; Drug Design; vztahy mezi strukturou a aktivitou; Alzheimerova nemoc; Magnetic Resonance Spectroscopy; cholinesterasové inhibitory; Cholinesterase Inhibitors; kinetika; Molecular Docking Simulation; ligandy; Humans